Peran Pendidikan Alternatif dalam Menanggulangi Siswa Putus Sekolah: The Role of Alternative Education in Tackling Students Dropout - Afif Muchlisin; Ahmad Zuber; Bagus Haryono (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2020)
The dropout rate is still relatively high in Surakarta. Many children cannot get an education from elementary to high school levels in Surakarta. The causative factors are economic that force children to work for daily needs and social environment that does not support learning activities. Alternatives education is one way to make economically disadvantaged people can get the education services needed. This study’s problem formulation is how alternative education reduces student dropout rates. This study aims to analyze and evaluate the alternative education programs to find effective methods to reduce student dropout rates at the Community Learning Center of Rumah Pelangi Sangkrah in Surakarta, Central Java Province, Indonesia. The theory used is Paulo Freire’s Conscientization Theory. The method used is Daniel Stufflebeam’s CIPP (Context, Input, Process, and Product) evaluation model with a qualitative research approach and conducting in-depth interviews with several informants and secondary data sources from related institutions. This evaluation study, one of which, in the context of Rumah Pelangi Sangkrah, it becomes one of the agencies that tackle students’ dropout due to the critical awareness of education actors and increased awareness of dropping out students. The strategy is to realize the importance of education with a personal approach to students’ dropout and parents. In terms of input, tutors’ availability is sufficient, but it is necessary to improve tutors’ welfare because the daily operational costs are already quite good. The learning process and the learning hour curriculum applied are very suited to the students’ condition. There are even alternative methods in online learning for students if they cannot attend class. In terms of output, through the ongoing program, Rumah Pelangi Sangkrah has been able to graduate the students through Package C Study Group of Equivalency Education Program to entrance several state universities using certificate equivalency.